EMISSIONS SECURE OF GLOBAL SATELLITE NAVIGATION SYSTEMS WITH USE OF METAMATERIAL SHIELDS - A. S. Abukraa; M. A. Vilkotsky; L. M. Lynkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of numerical and experimental analysis of the metamaterial shields effectiveness for use with the receiver antenna signals of global satellite navigation systemsare are given. From the many possible designs the screens with regular geometry design without curvature were chosen. Numerically, brute force, strictly periodic shields and shields of finite size were investigated. The suppressing interfering signals values of 8…10 dB were theoretically achieved. Experimental studies in the real situation, basically, confirmed it.